2021
DOI: 10.1186/s40168-021-01041-w
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-domain probiotic consortium as an alternative to chemical remediation of oil spills at coral reefs and adjacent sites

Abstract: Background Beginning in the last century, coral reefs have suffered the consequences of anthropogenic activities, including oil contamination. Chemical remediation methods, such as dispersants, can cause substantial harm to corals and reduce their resilience to stressors. To evaluate the impacts of oil contamination and find potential alternative solutions to chemical dispersants, we conducted a mesocosm experiment with the fire coral Millepora alcicornis, which is sensitive to environmental ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 99 publications
0
54
0
Order By: Relevance
“…Despite the diversity of the coral microbiome, which makes it challenging to decipher the contribution of associated microbes to coral holobiont biology, the dynamic nature of the coral microbiome, which can often change markedly-e.g., across sites, species, age, and under stress-further hampers the ability to conduct such studies in the natural environment (15,(19)(20)(21). For this reason, manipulation of BMCs in controlled experimental setups, such as mesocosms (22)(23)(24), provides an avenue to identify important microbial players and study holobiont responses (and putative underlying mechanisms), while maintaining a quasi-reef environment, to improve and inform the development of biotechnological solutions to promote coral reef resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diversity of the coral microbiome, which makes it challenging to decipher the contribution of associated microbes to coral holobiont biology, the dynamic nature of the coral microbiome, which can often change markedly-e.g., across sites, species, age, and under stress-further hampers the ability to conduct such studies in the natural environment (15,(19)(20)(21). For this reason, manipulation of BMCs in controlled experimental setups, such as mesocosms (22)(23)(24), provides an avenue to identify important microbial players and study holobiont responses (and putative underlying mechanisms), while maintaining a quasi-reef environment, to improve and inform the development of biotechnological solutions to promote coral reef resilience.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of such alarming challenges, recent advances in research have indicated the potential of microbiome-based interventions, such as probiotics to protect wildlife and mitigate environmental impacts, and microbiome transplants to restore ecosystems and improve their resilience [10][11][12][13][14][15][16][17][18][19][20][21] . We explore synergies between different disciplines, synthesize basic microbiome engineering and symbiosis concepts, and identify critical challenges and safety issues.…”
mentioning
confidence: 99%
“…[ 66 ] showed that coral bleaching could be reduced in the presence of the pathogen Vibrio coralliilyticus at normal and high temperatures. Although BMCs have been shown to aid in coral resistance [ 66,77–79 ] , [Santoro et al, 2021 ‐ https://advances.sciencemag.org/content/7/33/eabg3088] through the regulation of genes involved in the coral immune response and protection against heat stress (Santoro et al, 2021 ‐ https://advances.sciencemag.org/content/7/33/eabg3088), or even increase energy reserves and calcification rates, [ 80 ] the exact mechanisms producing the improved phenotype are not fully known. BMCs are chosen for their roles in coral holobiont nutrition and growth (via dimethylsulfoniopropionate degradation or increased cycling and provision of nutrients), removal of toxic compounds or stress mitigation (including decreasing intracellular ROS), early life development, and/or pathogen control.…”
Section: Microbial Modification Of Coral Epigenomes May Promote Healthmentioning
confidence: 99%
“…[8,76] By manipulating the microbiome of P. damicornis through the addition of beneficial microorganisms for corals (BMCs), Rosado et al [66] showed that coral bleaching could be reduced in the presence of the pathogen Vibrio coralliilyticus at normal and high temperatures. Although BMCs have been shown to aid in coral resistance [66,[77][78][79] increase energy reserves and calcification rates, [80] the exact mechanisms producing the improved phenotype are not fully known. BMCs are chosen for their roles in coral holobiont nutrition and growth (via dimethylsulfoniopropionate degradation or increased cycling and provision of nutrients), removal of toxic compounds or stress mitigation (including decreasing intracellular ROS), early life development, and/or pathogen control.…”
Section: Microbial Modification Of Coral Epigenomes May Promote Healthmentioning
confidence: 99%